World Economic Situation and Prospects 2018 - United Nations Department of Economic; Social Affairs (United Nations, 2018)
The United Nations definitive report on the state of the world economy, providing global and regional economic outlook for 2018 and 2019. Produced by the Department of Economic and Social Affairs, the five UN regional commissions, the United Nations Conference on Trade and Development, with contributions from the UN World Tourism Organization.